2020
DOI: 10.3390/polym12092129
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Recycling Options of (Nano)Enhanced CFRP Composite Prototypes Waste—A Life Cycle Perspective

Abstract: Life cycle assessment is a methodology to assess environmental impacts associated with a product or system/process by accounting resource requirements and emissions over its life cycle. The life cycle consists of four stages: material production, manufacturing, use, and end-of-life. This study highlights the need to conduct life cycle assessment (LCA) early in the new product development process, as a means to assess and evaluate the environmental impacts of (nano)enhanced carbon fibre-reinforced polymer (CFRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…The traditional waste disposal routes, namely landfill and incineration (energy recovery), have unfavourable environmental impacts. As mentioned in the literature [1,22,34], the hefty landfill taxation has established waste management industries to avoid landfills altogether. Furthermore, considering the price of vCFRP and vGFRP composites, the popularity of disposal via incineration has also reduced drastically.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional waste disposal routes, namely landfill and incineration (energy recovery), have unfavourable environmental impacts. As mentioned in the literature [1,22,34], the hefty landfill taxation has established waste management industries to avoid landfills altogether. Furthermore, considering the price of vCFRP and vGFRP composites, the popularity of disposal via incineration has also reduced drastically.…”
Section: Discussionmentioning
confidence: 99%
“…The applications of these products are given in Table 1 . For the PPE incineration process, the high-temperature energy produced from the waste PPE combustion can be used for generating mid-voltage electricity (energy recovery), which avoids the emissions of mid-voltage electricity production [ 58 ]. Like the landfilled waste plastic, the landfilled waste PPE produces negligible landfill gas, and it is not economically viable to use this gas to generate electricity [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that NMs (nano-silica asphalt mixtures) performed better in global warming, ozone depletion, eutrophication, photochemical oxidation, and ecotoxicity than conventional asphalt mixtures. Other examples of reviewed studies that did not perform until endpoint level are [79,87], which evaluated 10-12 midpoint categories for the use of nanostructured materials in building blocks and nano-enhanced, carbon fiber-reinforced polymer prototypes, respectively. By using NMs rather than conventional materials, environmental impacts can be reduced, especially for climate change, photochemical ozone depletion, particulate matter (human health and ecosystem), and acidification.…”
Section: Life Cycle Impact Assessment (Lcia)mentioning
confidence: 99%